CODE-SWITCHING: A COMMON PHENOMENON IN MULTILINGUAL SOCIETIES (International journal of artificial intelligence, 2025)
This study examines code-switching as a communicative strategy in multilingual societies, with a particular focus on its relevance in educational contexts. Through an interdisciplinary approach that integrates sociolinguistics and educational theory, the article highlights the functional and identity-driven motivations behind code-switching. Far from being a marker of linguistic deficiency, code-switching is shown to reflect high linguistic competence and cultural adaptability. The study provides insights into how this phenomenon can be embraced in classrooms to enhance learning outcomes.